Signal fires : a novel [large type] - Shapiro, Dani (Center Point Large Print, 2023)
"Signal Fires opens on a summer night in 1985. Three teenagers have been drinking. One of them gets behind the wheel of a car, and, in an instant, everything on Division Street changes. Each of their lives, and that of Ben Wilf, a young doctor who arrives on the scene, is shattered. For the Wilf family, the circumstances of that fatal accident will become the deepest kind of secret, one so dangerous it can never be spoken. On Division Street, time has moved on. When the Shenkmans arrive - a young couple expecting a baby boy - it is as if the accident never happened. But when Waldo, the Shenkmans' brilliant, lonely son who marvels at the beauty of the world and has a native ability to find connections in everything, befriends Dr. Wilf, now retired and struggling with his wife's decline, past events come hurtling back in ways no one could ever have foreseen."--